Differentially expressed microRNAs that target functional genes in mature soybean nodules. Issue 2 (10th May 2021) - Fan, Kejing; Wong‐Bajracharya, Johanna; Lin, Xiao; Ni, Meng; Ku, Yee‐Shan; Li, Man‐Wah; Tian, Chang Fu; Chan, Ting‐Fung; Lam, Hon‐Ming
Abstract: MicroRNAs (miRNAs) are important regulators of biological functions in plants. To find out what roles miRNAs play in regulating symbiotic nitrogen fixation (SNF) in soybean [ Glycine max (L.) Merr.], we identified high‐confidence differentially expressed (DE) miRNAs from uninoculated roots (UR), rhizobium‐inoculated roots (IR), and nodules (NODs) of soybean by robust small RNA sequencing (sRNA‐seq). Based on their predicted target messenger RNAs (mRNAs), the expression profiles of some of these DE miRNAs could be linked to nodule functions. In particular, several miRNAs associated with nutrient transportation genes were differentially expressed in IRs and mature NODs. MiR399b, specifically, was highly induced in IRs and NODs, as well as by inorganic phosphate (Pi) starvation. In composite soybean plants overexpressing miR399b, PHOSPHATE2 ( PHO2 ), a known target of miR399b that inhibits the activities of high‐affinity Pi transporters, was strongly repressed. In addition, the overexpression of miR399b in the roots of transgenic composite plants significantly improved whole‐plant Pi and ureide concentrations and the overall growth in terms of leaf node numbers and whole‐plant dry weight. Our findings suggest that the induction of miR399b in NODs could enhance nitrogen fixation and soybean growth, possibly via improving Pi uptake to achieve a better Pi–nitrogen balance to promote SNF in nodules. Core Ideas: Expression of some miRNAs in soybean roots or nodules is tissue specific. Some miRNAs regulate nutrient flow for nitrogen fixation in mature soybean nodules. MiR399b is highly induced in nodules and soybean roots inoculated with Sinorhizobium fredii . MiR399b can enhance phosphate and ureide contents in the whole soybean plant. MiR399b overexpression improves overall plant growth in soybean.